A Citrus Phosphate Starvation Response Factor CsPHL3 Negatively Regulates Carotenoid Metabolism. (25th January 2021) - Lu, Suwen; Ye, Junli; Zhu, Kaijie; Zhang, Yin; Zhang, Mengwei; Xu, Qiang; Deng, Xiuxin
Abstract: Carotenoids provide precursors for the biosynthesis of strigolactones, which are a new class of hormones that are essential in phosphate (Pi) signaling during plant development. Carotenoid metabolism is a finely tuned pathway, but our understanding of the regulation mechanisms is still limited. In this study, we isolated a protein designated as CsPHL3 from citrus. CsPHL3 belonged to the Pi starvation response factor (PHR)-like subclade and was upregulated by low Pi. Acting as a nucleus-localized protein with transactivation activity, CsPHL3 bound directly to activate the promoter of a key metabolic gene, lycopene β-cyclase1 ( LCYb1 ). Transgenic analysis revealed that the CsPHL3 -overexpressing tomato plants exhibited abnormal growth, like the plants grew under limited Pi conditions. The transgenic lines showed reduced carotenoid contents and elevated expression of LCYb genes but downregulation of other key carotenogenic genes, including phytoene synthase ( PSY ). Moreover, CsPHL3 induced anthocyanin biosynthesis and affected Pi signaling in the transgenic plants. We further demonstrated that the expression of PSY was negatively regulated by CsPHL3 and high Pi. It is concluded that CsPHL3 is a Pi starvation response factor that negatively regulates carotenoid metabolism by modulating the expression of carotenogenic genes. Establishment of the CsPHL3-CsLCYb1 network provides new valuable knowledge of the function and underlying mechanism of PHR transcription factors and expands our understanding of the complex regulation mechanisms of carotenoid biosynthesis.